Faktor yang Mempengaruhi Ekspor Crude Palm Oil (CPO) di Provinsi Kalimantan Timur - Pratama, Adnan Putra; Bustomi, Muhamad Yazid; Suosa Putra, Pandhu Rochman; Sardianti, Andi Lelanovita; Br Barus, Mika Debora (JURNAL AGRIBISNIS TERPADU, 2024)
The palm oil industry is currently the main supporting sector of the economy from the plantation sector with the main product being Crude Palm Oil (CPO). East Kalimantan is one of the provinces as the center of palm oil production in Indonesia. This study aims to determine the factors that affect East Kalimantan CPO exports with the Ordinary Least Square (OLS) method approach. The variables included are East Kalimantan CPO Exports (Y), East Kalimantan Palm Oil Production (X1), East Kalimantan Total Exports (X2), and East Kalimantan GRDP (X3). The results of the analysis show that the model used is free from classical assumptions so that it can be interpreted. The F-test results show that the variables of palm oil production, total exports, and GRDP together have a significant effect on East Kalimantan CPO exports. The t-test also shows that the variables of palm oil production, total exports, and GRDP each have an effect on East Kalimantan CPO exports. The variables of East Kalimantan palm oil production (X1) and East Kalimantan total exports (X2) have a positive and significant effect on total East Kalimantan CPO exports, while East Kalimantan GRDP (X3) has a negative and significant effect on total East Kalimantan CPO exports.